The homiletic structure of the Christian obituary and the role of the word of consolation for the bereaved - Andrei, Constantin (Technium Social Sciences Journal, 2023)
The aim of the Christian obituary is not to indoctrinate the faithful, but to train them, to bring hope, to create natural attitudes and constructive spiritual skills of man during life and in the face of death, to transmit Christian teachings for his salvation. This requires a commensurate sacrifice on the part of the preacher. In this context, the focus will be on the stages of preparation and elaboration of a Christian obituary, taking into account its special features. A special aspect that should not be neglected is related to the additions to the obituary that may be contrary to both local traditions and the teaching of faith. A special aspect that should not be neglected is related to the additions to the obituary that may be contrary to both local traditions and the teaching of faith. In such difficult moments resulting from the loss of a loved one, the priest must adapt his sermon in such a way as to include the essence of the Christian teaching about God’s providence and the meaning of the Christian life, about God’s reward after hard and long patience in suffering, offering consolation and peace to the bereaved family and those present at the funeral event. Therefore, thorough knowledge of Christian teaching, special and general training of the preacher are the essential conditions and stages for a successful sermon, for which he must train himself through spiritual, pastoral, cultural and intellectual effort, with time and without time, all his life.